2016
DOI: 10.1111/ijcs.12313
|View full text |Cite
|
Sign up to set email alerts
|

Time orientation and construal level: effects on eating and exercising behaviour and preferences

Abstract: Eating and exercising behaviour are both characterized by immediate and future consequences. Consequently, consideration of these consequences (i.e. time orientation) predicts eating and exercising behaviour. We investigate whether construal level acts as an underlying mechanism of these relations. Students (N = 101) completed measures of consideration of immediate and future consequences (i.e. CFC‐food and CFC‐exercise), construal level, eating and exercising behaviour and preferences. For self‐reported eatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Because participants with high continuation intentions of success place high value on, and enjoy exercise while achieving their goals, their intentions can be seen as those reflecting abstract construal. In empirical studies, abstract construal had a more positive effect on future preferences than did the concrete mind-set condition (Vilches-Montero & Spence, 2015), and the tendency to consider future consequence also increased (van Beek et al., 2017). Therefore, it can be concluded that, because participants who received FSF were induced to low-level construal, their continuation intentions of success reflecting an abstract mind-set decreased more in the posttest than in the pretest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because participants with high continuation intentions of success place high value on, and enjoy exercise while achieving their goals, their intentions can be seen as those reflecting abstract construal. In empirical studies, abstract construal had a more positive effect on future preferences than did the concrete mind-set condition (Vilches-Montero & Spence, 2015), and the tendency to consider future consequence also increased (van Beek et al., 2017). Therefore, it can be concluded that, because participants who received FSF were induced to low-level construal, their continuation intentions of success reflecting an abstract mind-set decreased more in the posttest than in the pretest.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, when importance is attached to a future-oriented goal and the value of exercise, the exercise intention is closer to a high-level construal than a low-level construal. Recent empirical studies have shown that abstract (or high-level) construal had a more positive effect on future preferences than did the concrete mind-set condition (or low-level construal) (Vilches-Montero & Spence, 2015), and as the tendency to consider future consequences became salient at the abstract construal level, preference for utilitarian foods products also increased (van Beek, Handgraaf, & Antonides, 2017). Therefore, participants’ continuation intentions of success can be enhanced more efficiently by providing them with DSF (emphasizing desirability) compared to FSF (emphasizing feasibility).…”
Section: Introductionmentioning
confidence: 99%
“…This evidence aligns with Construal Level Theory and its grounding notion of psychological distance (e.g., Trope & Liberman, 2010). If the immediate consequences of individuals' choices are mainly associated with a low‐level (concrete) construal (van Beek et al, 2017), then those who attach greater importance to the here‐and‐now are more sensitive to a taste‐related message, as it offers them an immediate reward that heightens their intention to spread positive word‐of‐mouth about the local dish.…”
Section: Discussionmentioning
confidence: 99%
“…Individual differences in construal level can influence judgments and choices: Those who tend to activate low (vs. high) construal‐level mindsets are more likely to prefer options construed at a low (vs. high) level (Han et al, 2014). Therefore, individuals' construal level might affect the effectiveness of taste‐ versus health‐related marketing communications, as temporally close (vs. distant) choices are likely to be associated with concrete (vs. abstract) construals (van Beek et al, 2017). In other words, communication messages focused on tastiness (vs. healthiness) should be more effective among consumers with a low‐level or concrete (vs. high‐level or abstract) construal.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation